2014
DOI: 10.1002/marc.201400018
|View full text |Cite
|
Sign up to set email alerts
|

Drastic Tuning of the Photonic Properties of «(Push–Pull)n» trans‐Bis(ethynyl)bis(Tributylphosphine)Platinum(II)‐Containing Polymers

Abstract: The trans-Pt(PBu3)2 Cl2 complex reacts with 1 equiv. of 2,6-diethynyl-AQ and 2 equiv. of 2-ethynyl-AQ (AQ = anthraquinone) to form the polymer (trans-Pt(2,6-diethynyl-AQ)2 (PBu3)2)n, 1, and the model compounds, 2, trans-Pt(PBu3)2 (2-ethynyl-AQ)2 (in a 20:1 ratio as trans-(2a) and cis-(2b) rotational isomers), respectively. These redox-active and luminescent materials have been characterized by gel permeation chromatography, thermal gravimetric analysis, X-ray crystallography, electrochemistry, photophysics, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…Conversely, P2 is weakly emissive at both 298 and 77 K upon exciting in the low‐energy absorption (i.e., λ exc = 400 nm; note that the blank experiment with the solvent alone was performed). This result comes as a surprise with respect to P0 , which exhibits a rather intense emission at 77 K (λ exc = 610 nm) arising from the CT 3 ( [Pt] → anthraquinone)* manifold, but not with respect to P3 , which does not show any emission from the lowest energy singlet and triplet excited states …”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Conversely, P2 is weakly emissive at both 298 and 77 K upon exciting in the low‐energy absorption (i.e., λ exc = 400 nm; note that the blank experiment with the solvent alone was performed). This result comes as a surprise with respect to P0 , which exhibits a rather intense emission at 77 K (λ exc = 610 nm) arising from the CT 3 ( [Pt] → anthraquinone)* manifold, but not with respect to P3 , which does not show any emission from the lowest energy singlet and triplet excited states …”
Section: Resultsmentioning
confidence: 87%
“…The synthesis of polymers P1 and P2 are shown in Scheme and the chemical steps are considered standard. Compounds a1 and b1 were obtained by reacting 1 with 4‐nitroaniline in a ratio of 1:1 and 1:2, respectively. After the removal of the TMS groups in compound b1 , the resulting intermediate b2 was obtained.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…P1 and P2 were found fluorescent from the lowest energy excited state at room temperature, thus drastically contrasting with the ( [Pt]-[AQ] ) n , ( [Pt]-[QI] ) n , and ( [Pt]-[AQI] ) n , polymers reported to be nonemissive or, at best, only luminescent in glassy matrices at 77 K. The absorption, excitation, and fluorescence spectra of 2a , 2b , M1 , M2 , P1 , and P2 in 2MeTHF at 298 K are presented in Figure , and the absorptivity data are summarized in Table . From an examination of the tails, where the 0–0 peak positions are expected (i.e., these tails spread, respectively, from ∼500 to ∼550 nm and from ∼525 to ∼575 nm for M1 and M2 and from ∼550 to ∼600 and from ∼550 to ∼625 nm for P1 and P2 , respectively), it is concluded that the 0–0 peak positions should be placed at lower energy for P1 and P2 in comparison with M1 and M2 .…”
Section: Resultsmentioning
confidence: 97%
“…To the best of our knowledge, the highest photoconversion efficiency (PCE) was recently reported to be 5.29% for a BHJSC containing the [Pt] moiety. , Concurrently, studies on complexes bearing [Pt] units indicated that the charge separated states are formed in the short picosecond (ps) time scale and that the [Pt] unit could mediate the electron transfer. Over the years, it was suggested that anchoring diphenylamine pendants as electron-rich groups , and using the electron-deficient anthraquinone, AQ , moiety , should improve the PCEs of [Pt] -containing materials for solar cells. Alternatively to ( [Pt] - [AQ] ) n polymers, polymers containing anthraquinone diimine, AQI (i.e., ( [Pt]-[AQI] ) n ), were also designed. , These latter materials are nonemissive at room temperature (RT), but exhibit both low potential oxidation and reduction processes, , rendering them suitable for photoinduced electron transfers processes. Despite the fact that [Pt] is a common synthon and its relevance to its use in solar cells, there is, to the best of our knowledge, no investigation reporting the rates of photoinduced electron transfer between [Pt] and an electron acceptor.…”
Section: Introductionmentioning
confidence: 99%